2003
DOI: 10.1097/00129492-200309000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Cochleosaccular Endolymphatic Hydrops without Vertigo Revealed by Furosemide-Loading Vestibular Evoked Myogenic Potential Test

Abstract: The patients in cases 2 and 3 complained of a short-lasting sensation of falling down. Severe disequilibrium that prohibited standing up was noted in all cases. It was suggested that these symptoms were caused by saccular hydrops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…There are authors who assume that the balance problems associated with otosclerosis are caused by saccular dysfunction originating from endolymphatic or saccular hydrops [3639] or direct invasion of the otosclerotic focus to the saccular macula or saccular afferents [35,40]. A 2012 study by Saka et al [33] found that balance problems in otosclerosis were associated with abnormal results for BC-VEMP.…”
Section: Discussionmentioning
confidence: 99%
“…There are authors who assume that the balance problems associated with otosclerosis are caused by saccular dysfunction originating from endolymphatic or saccular hydrops [3639] or direct invasion of the otosclerotic focus to the saccular macula or saccular afferents [35,40]. A 2012 study by Saka et al [33] found that balance problems in otosclerosis were associated with abnormal results for BC-VEMP.…”
Section: Discussionmentioning
confidence: 99%
“…fluctuating hearing loss, tinnitus, and recurrent vertigo. Seo et al [17] reported that patients with cochleosaccular hydrops revealed by VEMP did not complain of any recurrent vertigo but of recurrent short-lasting disequilibrium. Three patients in our series suffered from recurrent disequilibrium lasting for a short duration (cases 1, 4, and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Seo et al . [15] described three cases without vertigo, involving patients with cochleosaccular endolymphatic hydrops, revealed by furosemide-loading vestibular evoked myogenic potential test.…”
Section: Discussionmentioning
confidence: 99%